Many ways to learn a kid's guide to LD - Stern, Judith M. (Magination Press, 2011)
Provides advice and encouragement for children with learning disabilities, including tips and strategies for succeeding in school, and addresses the social issues children with learning disabilities may face in the classroom and out.